Experimental game played between input dealers and farmers - CGIAR Research Program on Agriculture for Nutrition and Health (2017)
Researchers piloted and implemented experiment in Bangladesh in 2016, now presenting a paper based on the experiment results at conferences (Experimental Sciences Association design confernece, May 2016; presentations at Michigan State University and ICABR conference, 2018); paper will be complete later this year and submitted to a journal.